FACTORS ENSURING SUSTAINABILITY OF INDUSTRIAL ENTERPRISES DURING DIGITAL TRANSFORMATION (Marketing Journal, 2025)
This article provides a systematic analysis of the factors ensuring the economic sustainability of industrial enterprises under digital transformation conditions . The study examines the experience of leading countries (Germany, South Korea, and China) in achieving sustainable industrial growth through the implementation of digital technologies such as IoT, Big Data, AI, ERP, and Blockchain. Based on theoretical approaches to assessing economic stability, the article identifies the impact of internal and external factors — including the development level of digital infrastructure, innovation activity, digital management culture, and human capital. Furthermore, it proposes organizational and economic mechanisms for ensuring sustainable industrial performance and presents a model integrated with digital transformation factors. The findings have practical significance for developing strategies to enhance the sustainabil ity of industrial enterprises in Uzbekistan through digital solutions.
Keywords: digital transformation; economic sustainability; industrial enterprises; digital technologies; innovative development; organizational -economic mechanism; sustainable development